PENCARIAN INFORMASI OLEH FOODIE PADA FOTO MAKANAN DI INSTAGRAM - Aprilia, Monika Pretty (Unitri Press, 2020)
Information seeking reduces uncertainty. Information is needed by human for work needs and other daily activities. One of these activities is a hobby. Many people spend a lot of time and money when they seek information for a hobby rather than for work. Foodie is a person who loves food. Foodie is interested in learning and trying new food. When someone is called a foodie then they must be someone who loves to taste food. A foodie also needs information to be able to taste various food. Social media has become one of information sources used by foodie to get information that related to food. This research shows the process of information seeking by foodie on food photos in Instagram. This study used consumer behavior in the pre-purchase stage of service consumption from Tsiotsou and Wirtz?s theory. Its method was descriptive qualitative by interviewing five foodies who live in Jakarta. Research result shows that Instagram is the main source for foodie when they seek information that related to food such as dining place information.